The Halifax Hellions - Vasti, Alexandra (St. Martin's Griffin, 2026)
"From USA Today bestselling author Alexandra Vasti comes The Halifax Hellions: a pair of sexy, hilarious romps in which the most scandalous ladies in London finally meet their match. From the day of their debut, when Matilda smoked a cheroot and Margo tied a cherry stem in a knot with her tongue, the Halifax twins have flouted convention at every turn. But when Matilda runs off with the dangerous Marquess of Ashford-who has every reason to hate her-she may have gone a bit too far. Determined to stop Matilda's inexplicable elopement, her sister Margo turns to her oldest friend for help: because if anyone can get her to Scotland in time, it's starchy solicitor Henry Mortimer. But the road to Scotland is paved with secrets. Beneath his buttoned-up exterior, Henry is ardently, wildly, miserably in love with Margo. And Matilda and Ashford's relationship too may not be quite what it seems. Between salacious engravings, secret identities, and demanding feral cats, nothing about the journey goes as planned. With the Halifax Hellions at the reins, a week in a carriage is exactly enough time to turn the world upside down . . . and, perhaps, find the love stories they never expected. For the first time ever in print, The Halifax Hellions brings together Margo and Matilda's novellas, along with a swoony new epilogue"-- Provided by publisher.